Mixed FE–MB methodology for the evaluation of passive safety performances of aeronautical seats. Issue 3 (4th May 2019) - di Napoli, F.; De Luca, A.; Caputo, F.; Marulo, F.; Guida, M.; Vitolo, B.
ABSTRACT: The certification of aircraft seats involves the investigation of the structural performance of their components under emergency landing conditions. . The paper reports the activities related to an experimental sled-test of a single row of two seats placed in front of a stiff fuselage bulkhead, by considering a single anthropomorphic dummy arranged on one of the seats. Tests have been developed at the facility equipped with a sled decelerator testing system compliant with certification requirements from FAR25 for TSO C127a regulations. Four different numerical models have been developed in order to simulate the experimental test: a full-FE modelby LSTC-LsDyna® code, a full-MB modeland a hybrid FE/MB developed using by TNO-Madymo® code and a Coupled FE/MB model. Numerical results achieved by these models have been compared with experimental ones, in order to assess their use for CBA (certification by analysis) purposeto be applied since the preliminary design phase of the seat.